Impact of Diabetes in Patients with Pulmonary Hypertension. (March 2015) - Abernethy, Abraham D.; Stackhouse, Kathryn; Hart, Stephen; Devendra, Ganesh; Bashore, Thomas M.; Dweik, Raed; Krasuski, Richard A.
Diabetes complicates management in a number of disease states and adversely impacts survival; how diabetes affects patients with pulmonary hypertension (PH) has not been well characterized. With insulin resistance having recently been demonstrated in PH, we sought to examine the impact of diabetes in these patients. Demographic characteristics, echo data, and invasive hemodynamic data were prospectively collected for 261 patients with PH referred for initial hemodynamic assessment. Diabetes was defined as documented insulin resistance or treatment with antidiabetic medications. Fifty-five patients (21%) had diabetes, and compared with nondiabetic patients, they were older (mean years ± SD, 61 ± 13 vs. 56 ± 16; P = 0.02), more likely to be black (29% vs. 14%; P = 0.02) and hypertensive (71% vs. 30%; P < 0.001), and had higher mean (±SD) serum creatinine levels (1.1 ± 0.5 vs. 1.0 ± 0.4; P = 0.03). Diabetic patients had similar World Health Organization functional class at presentation but were more likely to have pulmonary venous etiology of PH (24% vs. 10%; P = 0.01). Echo findings, including biventricular function, tricuspid regurgitation, and pressure estimates were similar. Invasive pulmonary pressures and cardiac output were similar, but right atrial pressure was appreciably higher (14 ± 8 mmHg vs. 10 ± 5 mmHg; P < 0.001). Despite similar management, survival was markedly worse and remained so after statistical adjustment. In summary, diabetic patients referred for assessment of PH were more likely to have pulmonary venous disease than nondiabetic patients with PH, with hemodynamics suggesting greater right-sided diastolic dysfunction. The markedly worse survival in these patients merits further study.